PATTERNS AND OUTCOMES OF PENETRATING NECK INJURIES AT LIAQUAT UNIVERSITY HOSPITAL, HYDERABAD - PAKISTAN (The Research of Medical Science Review, 2025)
Objective: To determine the frequency of various types of penetrating neck injuries and their outcomes at Liaquat University Hospital, Hyderabad - PakistanMethods: This cross-sectional-descriptive-study was conducted from 05-09-2024 to 05-03-2025 at Liaquat University Hospital. A total of 145 patients aged 18–65 years with penetrating neck injuries were included via non-probability consecutive sampling. Data on demographic variables, injury types, anatomical zones, and outcomes were collected using a structured questionnaire. Analysis was done in SPSS v21.0 using descriptive statistics and chi-square test (p ≤ 0.05).Results: The mean age was 35.5 ± 12.4 years; 65.5% were males. Zone II injuries were most frequent (34.5%), followed by Zone I (24.1%) and Zone III (20.7%). Stab wounds (34.5%) and gunshot wounds (31.0%) were the predominant mechanisms. Vascular injuries were most common (41.4%). Mechanical ventilation was required in 27.6% of patients (mean 5.2 ± 2.1 days). Mean hospital stay was 8.4 ± 3.7 days. Overall mortality was 6.9%, with statistically significant associations between mortality and both age (p = 0.011) and gender (p = 0.038).Conclusion: Penetrating neck injuries are predominantly due to stab and gunshot wounds, with Zone II and vascular structures most commonly affected. Younger age and male gender are associated with higher mortality, underscoring the need for targeted trauma care strategies in low-resource settings.